15N/14N ratio and quality control of Iberian pig carcasses - Delgado Huertas A.; De Pedro Sanz E.; García Olmo J.; Reyes E. (5. International Symposium on the Mediterranean Pig, 2007)
The aim of this study is to evaluate the possible use of the 15N/14N index as a means of determining the feeding regime of Iberian pigs. Two batches of Iberian pigs (B1 and B2) were fed on fallen acorns and fodder (montanera) during their final fattening stage and two batches (C1 and C2) ate only commercial feed. The feed consumed by batch C2 was a special feed, designed to achieve a fatty acid profile similar to that produced when the animals eat acorns (bellota). The 15N/14N isotope ratio was determined in each animal, in loin samples in addition to the fatty acid content in samples of subcutaneous fat taken from the animals' hindquarters. According to the Official Sales Contract of Iberian pigs (OSC), the batches were classified as Recebo (B1 and C2), Bellota (B2) and Cebo (C1). The d15 N isotope values enables the groups of animals to be classified according to their feeding regime, including the two batches fed on commercial feed.
5. International Symposium on the Mediterranean Pig, 2004/09/16-19, Tarbes (France)